2014
DOI: 10.1007/s00216-014-8028-9
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of gram-positive and gram-negative bacteria by antibacterial porous polymeric monolith formed in microfluidic biochips for sample preparation

Abstract: Bacterial cell lysis is demonstrated using polymeric microfluidic biochips operating via a hybrid mechanical shearing/contact-killing mechanism. These biochips are fabricated from a cross-linked poly(methyl methacrylate) (X-PMMA) substrate by well-controlled, high-throughput laser micromachining. The unreacted double bonds at the surface of X-PMMA provide covalent bonding for the monolith, thus contributing to the mechanical stability of the biochip and eliminating the need for surface treatment. The lysis eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The antimicrobial polymers have the ability to inhibit microbial organisms by killing them. The same group later improved the efficiency of lysis (89%) by regulating the hydrophobic–hydrophilic property of the PPM [ 50 ]. They also suggest that use of PPM did not inhibit the PCR amplification process.…”
Section: Lysis Techniquesmentioning
confidence: 99%
“…The antimicrobial polymers have the ability to inhibit microbial organisms by killing them. The same group later improved the efficiency of lysis (89%) by regulating the hydrophobic–hydrophilic property of the PPM [ 50 ]. They also suggest that use of PPM did not inhibit the PCR amplification process.…”
Section: Lysis Techniquesmentioning
confidence: 99%
“…These monoliths allowed specific capture of Rickettsia typhi, and subsequent immunofluorescent staining and imaging of the bacteria inside the chip indicated detection limits of about 100 bacteria per ml of blood sample. Aly et al 90,91 developed a method for lysis of both gram-positive and gram-negative bacteria using a monolith based on in-house-synthesized N-(tert-butyloxycarbonyl) aminoethyl methacrylate, which has antibacterial properties. The influence of the flow rate and of the hydrophilic-lipophilic balance in the monolith on the cell lysis efficiency was investigated, and they found that the contribution of contact killing to cell lysis was more significant than that of mechanical shearing.…”
Section: A Analysis Of Vesicles and Bacteriamentioning
confidence: 99%
“…The development of antibacterial materials with nanostructured features has shown promising results for reducing the adhesion on surfaces [ 17 , 18 ] or even killing bacteria due to the fact that cells respond to nanostructures of specific topography by deforming or extended stretching of their membrane [ 19 , 20 , 21 ], resulting to cell piercing or rupture [ 22 , 23 , 24 , 25 , 26 ]. The most well-known materials with active antibacterial properties are nanosized metal oxide compounds and nanostructures thereof (TiO 2 , ZnO, CuO) which are exploited as antimicrobial surfaces [ 19 , 27 , 28 ], as well as in microfluidic and highly efficient analytical platforms [ 29 ].…”
Section: Introductionmentioning
confidence: 99%